2020
DOI: 10.1016/j.ifset.2019.102253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure processing on heat-induced gelling capacity of blue crab (Callinectes sapidus) meat

Abstract: There has been increasing use of High pressure processing (HPP) in the fishery industry since this technology facilitates shellfish shucking. Nevertheless, there is limited information about the effect of HPP on protein functional properties of some shellfish. In the case of blue crab meat it is important to study the effect of HPP on protein functional properties such as gelling capacity in order to optimize processing parameters for the preparation of high-quality restructured products. This paper reports th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…These changes were lessened in salmon treated by HPP (300 MPa for 10 min) at low temperature (i.e., at 5 • C compared to 40 • C) and the use gelatin-lignin film, which resulted in better salmon quality. Similar uses of FT-IR to examine the protein structure of blue crab meat subjected to HPP treatment [125,187], palm ruff treated by HPP [188], and shrimp treated by ultrasound processing [186] have been reported. These studies confirmed that HPP treatment (100, 300, and 600 MPa for 5 min at 10 • C) and ultrasound processing (20-kHz frequency, 400 W for various times at room temperature) resulted in a lower percentage of α-helix and a higher percentage of β-turn secondary structures compared to untreated samples.…”
Section: Non-thermal Treatmentsmentioning
confidence: 73%
“…These changes were lessened in salmon treated by HPP (300 MPa for 10 min) at low temperature (i.e., at 5 • C compared to 40 • C) and the use gelatin-lignin film, which resulted in better salmon quality. Similar uses of FT-IR to examine the protein structure of blue crab meat subjected to HPP treatment [125,187], palm ruff treated by HPP [188], and shrimp treated by ultrasound processing [186] have been reported. These studies confirmed that HPP treatment (100, 300, and 600 MPa for 5 min at 10 • C) and ultrasound processing (20-kHz frequency, 400 W for various times at room temperature) resulted in a lower percentage of α-helix and a higher percentage of β-turn secondary structures compared to untreated samples.…”
Section: Non-thermal Treatmentsmentioning
confidence: 73%
“…The color parameters ( L , a , and b ) of crayfish meat gels prepared from freeze-thawed crayfish were displayed in Figure 3 D. A freeze-thawing cycle of crayfish prior to gel preparation led to a significant decrease in the L values of the subsequent heat-induced gels ( p < 0.05), compared with CG (untreated crayfish). Previous literature reported that the high value of lightness in gels could be related to protein aggregation, and the increased cross-links promote a compact structure, leading to a greater area of light reflectance [ 32 ]. The decrease in the whiteness of protein gels from mirror carp was due to the freezing-induced denaturation of MPs, and protein denaturation could reduce the free water content in the gel network structure, which decreased the reflection [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…< 0.05), compared with CG (untreated crayfish). Previous literature reported that the high value of lightness in gels could be related to protein aggregation, and the increased crosslinks promote a compact structure, leading to a greater area of light reflectance [32]. The decrease in the whiteness of protein gels from mirror carp was due to the freezing-induced denaturation of MPs, and protein denaturation could reduce the free water content in the gel network structure, which decreased the reflection [6].…”
Section: Whc and Sem Of Gelsmentioning
confidence: 96%
“…These severe conditions contribute to a significant loss in moisture and extraction yield. HPP treatment (100–300 MPa) improved the gelling properties of crab meat proteins and enhanced meat extraction yield compared to the thermal treatment (90°C for 20 min) (Martínez‐Maldonado et al., 2020, 2017). This was attributed to HPP that induced conformational changes, structural transformations, and partial denaturation of myofibrillar proteins, leading to an increase of WHC.…”
Section: Hpp Applications With Shellfishmentioning
confidence: 99%